Two-Stage Liver Transplantation with Temporary Porto-Middle Hepatic Vein Shunt - Giovanni Varotti; Enzo Andorno; Marco Casaccia; Stefano Di Domenico; Giuliano Bottino; Pietro Diviacco; Nicola Morelli; Chiara Ferrari; Roberto Ferrante; Umberto Valente (Journal of Transplantation)
Two-stage liver transplantation (LT) has been reported for cases of fulminant liver failure that can lead to toxic hepatic syndrome, or massive hemorrhages resulting in uncontrollable bleeding. Technically, the first stage of the procedure consists of a total hepatectomy with preservation of the recipient's inferior vena cava (IVC), followed by the creation of a temporary end-to-side porto-caval shunt (TPCS). The second stage consists of removing the TPCS and implanting a liver graft when one becomes available. We report a case of a two-stage total hepatectomy and LT in which a temporary end-to-end anastomosis between the portal vein and the middle hepatic vein (TPMHV) was performed as an alternative to the classic end-to-end TPCS. The creation of a TPMHV proved technically feasible and showed some advantages compared to the standard TPCS. In cases in which a two-stage LT with side-to-side caval reconstruction is utilized, TPMHV can be considered as a safe and effective alternative to standard TPCS.